Notes for the history of health care in sarare, state of lara, venezuela. (Revista Venezolana de Salud Pública, 2018)
This essay has the purpose of contributing to the historical reconstruction of the processes, protagonists and health care institutions of Sarare, in the Simón Planas municipality of the } Lara state between the 18th and 19th centuries; also contributing in this way to the social history, to the citizen identity and to the regional history of the medical sciences.
Keywords: Venezuela; Sarare; History